A new hypothesis of sex-differences in temporomandibular disorders: Estrogen enhances hyperalgesia of inflamed TMJ through modulating voltage-gated sodium channel 1.7 in trigeminal ganglion?. Issue 2 (February 2015) - Bi, Rui-Yun; Ding, Yun; Gan, Ye-Hua
Abstract: Objective: Temporomandibular disorders (TMD) are an assorted set of clinical conditions characterized mainly by pain in the temporomandibular joint (TMJ). TMJ inflammation or synovitis is frequently observed in TMD patients and is the major reason for TMD pain. TMD is prevalent in women of childbearing age, at least twice than in men, implying that estrogen may be involved in TMD pain processing. Estrogen affects a cell mainly through the estrogen receptors (ER). The estrogen–ER complex binds to estrogen response element sequences (ERE) in the promoter region of specific genes and then exerts its regulatory potential. The voltage-gated sodium channel 1.7 (Nav1.7), whose single disruption leads to a complete loss of pain, amplifies weak stimuli in the neurons and acts as the threshold channel for firing action potentials and plays a prominent role in pain perception, including inflammatory pain. Furthermore, our previous study showed that trigeminal ganglionic Nav1.7 was involved in the hyperalgesia of the inflamed TMJ. We propose that estrogen may enhance hyperalgesia of inflamed TMJ through decrease nociceptive threshold of TMJ or inflamed TMJ by modulating both expression and channel threshold of Nav1.7 in trigeminal ganglion.